COVID-19, communication and culture beyond the global workplace - Buckwalter, Elvis; Rossette-Crake, Fiona (Abingdon, Oxon, [England] Routledge, an imprint of the Taylor & Francis Group, 2023)
"This book analyses some of the many upheavals brought about by the COVID-19 pandemic through the lens of the COVID-19-communication-culture interface, with a particular focus on the new global, virtual workplace. It brings together a pluridisciplinary and multinational team of researchers from the fields of sociology and organisational studies, discourse analysis, linguistics, communication and cultural studies, and includes testimonials from actors within the professional sector such as international managers, consultants and foreign trade advisors. The collection examines a wide range of phenomena including communication on the pandemic by public authorities, the pandemic as a discursive construct, the digital turn and its impact on communication, the role of social media, as well as national diplomacy and questions of surveillance, (bio)power and trust. Issues pertaining specifically to the workplace focus on the impact of remote work, including the challenge of building cohesive work relations and managing cultural difference, distance recruitment, the new forms of professional online communication, the future of the remote work model and questions of identity that are underpinned by the culture of professions. It aims to theoretically inform some of the enormous changes which have been brought about by the COVID-19 pandemic at multiple levels of our professional and social lives. It concludes with a virtual round-table discussion on the question of cultural difference with respect to both the pandemic itself and to work practice. COVID-19, Communication and Culture: Beyond the Global Workplace will be of great interest to academics and professionals interested in the communication and discourse and the cultural impact of COVID-19"--Provided by publisher.
Preface / J. Michael Ryan -- COVID-19, communication, culture and the workplace, multiple spaces, multiple interfaces / Fiona Rossette-Crake and Elvis Buckwalter -- Responding to the pandemic : a discourse analysis approach / Dominique Maingueneau -- Wikipedia as a trusted method of information assessment during the COVID-19 crisis / Antonin Segault -- Understanding China's "intermestic" online vaccination-themed narrative strategy : towards a "Global community of health for all"? / Zhao Alexandre Huang and Rudong Zhang -- Formulating a discourse of solidarity amid COVID-19 : a positive discourse analysis of remarks given by spokespersons from China's foreign ministry / Yating Yu and Dennis Tay -- COVID-19 and communication through the lens of culture / Elvis Buckwalter -- Why face-to-face communication matters : a comparison of face-to-face and computer-mediated communication / Almut Koester -- COVID-19 and the rise of digitalised spoken communication : the example of webinars / Fiona Rossette-Crake -- Managing multilingual teams in a virtual context / Helene Tenzer -- Communicating on the job during COVID-19 : some professional testimonials / Leticia Correa do Carmo, Maria Martha Gomez Villalon, Océane Juste, Juan Pinargote, Perrine Rozec -- Remote work and the contemporary workplace : the example of student internships in the context of France / Danièle Linhart -- COVID-19 and the culture of professions : issues and tensions in the group of health professionals / Sylvie Parrini-Alemanno -- From privilege to duty : changing media representations of remote work in France, the USA and Estonia / Raili Marling and Marge Käsper -- International managers and expatriates in the face of the pandemic : impact and cultural issues / Corinne Saurel -- Working internationally during COVID-19 : professional testimonials / Lucille Boulet, Olivier Motard and Samira Touam -- Concluding virtual round-table discussion : COVID-19, communication, culture and work practice / Fiona Rossette-Crake and Elvis Buckwalter.
Includes bibliographical references and index.
Keywords: Communication in organizations; Telecommuting; Work environment; Communication and culture; COVID-19 Pandemic, 2020- -- Social aspects; COVID-19 Pandemic, 2020- -- Influence